Beware of Financial Repression: Lessons from History - Andreas Hoffmann (Intereconomics, 2019)
As austerity policies are unpopular with voters and high debt levels are a drag on growth, several economists, most famously Carmen Reinhart and Kenneth Rogoff, have suggested that governments might have to consider an extra dose of financial repression as a way out of the low growth-high debt trap. I argue that the history of advanced economies under Bretton Woods and the liberalisation experience of the lagging countries suggest that an exit from financially repressive policies is the better alternative to promote growth and the sustainability of government finances.
Keywords: 330